Association study of high-frequency variants of MTHFR gene with retinal vein occlusion in a Spanish population - Fernández-Vega, Beatriz; Álvarez, Lydia; García, Montserrat; Artime, Enol; González Fernández, Adrián; Fernández-Vega, Carlos; Nicieza, Javier; Vega, José A.; González-Iglesias, Héctor (Ophthalmic genetics, 2019)
: To study the association of the most common methylenetetrahydrofolate reductase ( ) genetic polymorphisms C677T and A1298C with retinal vein occlusion (RVO) in a Spanish population. : Case-control study involving 359 subjects, 183 unrelated native Spanish patients diagnosed with RVO, distributed in central or branch RVO, and 176 healthy controls. Two SNPs located in the gene , C677T (rs1801133) and A1298C (rs1801131) were analyzed by DNA sequencing and TaqMan assays. : A high prevalence of the variants T and C of the SNP C677T and A1298C, respectively, was observed in our population. Specifically, 88.07% of controls and 85.25% of RVO patients have at least one of these variants. However, the prevalence of these variants was not significantly different when comparing RVO patients and controls. The variant T of C677T was identified in 60.65% of RVO patients and 59.10% of control subjects, while the variant C of A1298C was present in 46.45% of RVO patients and 51.14% of controls. No association of dyslipidemia, diabetes mellitus, glaucoma, thyroid disease and renal disease with RVO was observed, while hypertension was significantly higher in the RVO patients ( < .0001). : The variants, T of C677T and C of A1298C, did not significantly increase the risk of suffering RVO in a Spanish population and therefore additional risk factors are contributing to the onset of the disease.